The Collagen-binding Integrin α2β1 Is a Novel Interaction Partner of the Trimeresurus flavoviridis Venom Protein Flavocetin-A - Arlinghaus, Franziska T. (American Society for Biochemistry and Molecular Biology, 2013)
Many snake venoms are known for their antithrombotic activity. They contain components that specifically target different platelet-activating receptors such as the collagen-binding integrin α2β1 and the von Willebrand factor receptor GPIb. In a search for an α2β1 integrin-blocking component from the venom of the habu snake (Trimeresurus flavoviridis), we employed two independent purification protocols. First, we used the integrin α2A domain, a major collagen-binding domain, as bait for affinity purification of an α2β1 integrin-binding toxin from the crude venom. Second, in parallel, we used classical protein separation protocols and tested for α2β1 integrin-inhibiting capabilities by ELISA. Using both approaches, we identified flavocetin-A as an inhibitor of α2β1 integrin. Hitherto, flavocetin-A has been reported as a GPIb inhibitor. However, flavocetin-A inhibited collagen-induced platelet aggregation even after GPIb was blocked with other inhibitors. Moreover, flavocetin-A antagonized α2β1 integrin-mediated adhesion and migration of HT1080 human fibrosarcoma cells, which lack any GPIb, on collagen. Protein chemical analyses proved that flavocetin-A binds to α2β1 integrin and its α2A domain with high affinity and in a cooperative manner, which most likely is due to its quaternary structure. Kinetic measurements confirmed the formation of a strong complex between integrin and flavocetin-A, which dissociates very slowly. This study proves that flavocetin-A, which has long been known as a GPIb inhibitor, efficiently targets α2β1 integrin and thus blocks collagen-induced platelet activation. Moreover, our findings suggest that the separation of GPIb- and α2β1 integrin-blocking members within the C-type lectin-related protein family is less strict than previously assumed.